Effects of Prenatal Drug Exposure on Children's Working Memory: A Systematic Review - Samariz Laboy-Hernández; Nelson D. Cruz-Bermúdez; Guillermo Bernal (Korean Child Neurology Society, 2020)
Purpose Substance use during pregnancy is a public health problem. Prenatal drug exposure (PDE) is linked to abnormal physical growth, altered brain organization, and cognitive, emotional, and behavioral problems later in life. Working memory (WM) plays an important role in the cognitive processes required for academic achievement, particularly for problem-solving, planning, and decision-making. The purpose of this study was to conduct a systematic review of studies measuring the effect of PDE on children's WM. Methods Using the Joanna Briggs Institute Reviewers' Manual, we systematically reviewed eight studies (published 2008 to 2019) that measured the effects of PDE on WM among children ages 5 to 12. Results Studies measuring prenatal exposure to methamphetamine, tobacco, or cocaine did not find differences in WM between PDE groups and controls. Nonetheless, three of the studies found that alcohol had negative effects on children's WM, pinpointing the potential of alcohol to disrupt neurocognitive development. Conclusion We were not able to generate conclusions regarding the consequences of PDE on children's WM, but we discuss methodological issues and implications for future research on this phenomenon.